2017
DOI: 10.1002/prot.25323
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-based analysis of protein degradation rates

Abstract: Protein turnover is a key aspect of cellular homeostasis and proteome dynamics. However, there is little consensus on which properties of a protein determine its lifetime in the cell. In this work, we exploit two reliable datasets of experimental protein degradation rates to learn models and uncover determinants of protein degradation, with particular focus on properties that can be derived from the sequence. Our work shows that simple sequence features suffice to obtain predictive models of which the output c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
(69 reference statements)
2
21
0
Order By: Relevance
“…In our models the degrons, including the N-degrons, were features of negligible importance for the prediction of protein lifetimes. This is in line with a recent study that also found little support for the N-end rule in a computational analysis of protein degradation rates in cell cultures 35 . This does not argue against the importance of degrons, or against the N-end rule.…”
Section: Discussionsupporting
confidence: 91%
“…In our models the degrons, including the N-degrons, were features of negligible importance for the prediction of protein lifetimes. This is in line with a recent study that also found little support for the N-end rule in a computational analysis of protein degradation rates in cell cultures 35 . This does not argue against the importance of degrons, or against the N-end rule.…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly important since, analogous to our Sup35 reporter assay, isolated protein fragments are commonly used to initially define regulatory principles, which are then subsequently applied to full-length proteins in their native contexts. Indeed, our data are consistent with numerous previous studies indicating that relationships between protein sequence and degradation rates are rarely absolute on a proteome-wide scale, and degradation rate for a given protein likely results from the culmination and integration of multiple regulatory signals [55][56][57][58][59][60]. Therefore, other factors such as protein localization, proteinprotein interaction, or neighboring protein sequences could influence the proteostatic regulation of proteins containing G-rich and Q/N-rich LCDs.…”
Section: Discussionsupporting
confidence: 91%
“…The CTD is rich in proline (11%) and arginine (9%) residues and most probably intrinsically disordered. Sequence comparison revealed a prion-like domain (PrlD) 26 and putative PEST sequences 27 , which most probably relate to lower stability of the protein because of their intrinsic disorder 28 .…”
Section: Resultsmentioning
confidence: 99%